2009
DOI: 10.1016/j.cca.2009.03.051
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between TG vs remnant lipoproteins in the fasting and postprandial plasma of 23 volunteers

Abstract: Background-Two recent publications report that non-fasting triglycerides concentrations in plasma are more predictive of cardiovascular events than conventional measurements of fasting triglycerides. While these observations are consistent with the previous studies, direct correlations between remnant lipoprotein triglyceride (RLP-TG) and remnant lipoprotein cholesterol (RLP-C), which are also considered to be risk factors for cardiovascular disease, and fasting and postprandial TG have not been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 22 publications
2
19
0
1
Order By: Relevance
“…This observation is in accordance with the previous reports that demonstrated high correlation between plasma VLDL-C and TG concentrations, at least in the healthy subjects [40,41]. Also, the plasma TG concentrations are known to reflect plasma VLDL-C concentrations, regardless of the fasting and postprandial states [40].…”
Section: Discussionsupporting
confidence: 91%
“…This observation is in accordance with the previous reports that demonstrated high correlation between plasma VLDL-C and TG concentrations, at least in the healthy subjects [40,41]. Also, the plasma TG concentrations are known to reflect plasma VLDL-C concentrations, regardless of the fasting and postprandial states [40].…”
Section: Discussionsupporting
confidence: 91%
“…We reported that non-fasting TG correlated more strongly with remnant lipoproteins than fasting TG [43]. The correlations between postprandial TG and remnant lipoprotein concentrations were significantly more robust when compared with fasting TG vs remnant lipoprotein concentrations.…”
Section: Daily Rhythm Of Plasma Cholesterol Tg and Remnant Lipoprmentioning
confidence: 99%
“…We reported that nonfasting TG correlated more strongly with remnant lipoproteins than fasting TG [79]. The correlation between postprandial TG and remnant lipoprotein was significantly more robust when compared with fasting TG versus remnant lipoprotein.…”
Section: Daily Rhythm Of Plasma Tg Apob-48 and Remnant Lipoproteinsmentioning
confidence: 82%
“…Most increased TG after food intake represented increased remnant lipoproteins, $80%. Thus, remnant TG ¼ (postprandial TG À fasting TG) Â 0.8 [79].…”
Section: Daily Rhythm Of Plasma Tg Apob-48 and Remnant Lipoproteinsmentioning
confidence: 99%